NILAI SUSILA DALAM SUSASTRA HINDU DAN IMPLEMENTASINYA PADA KEHIDUPAN SEHARI-HARI - Mardika, Made; Pratama, Gede Nanda Jaya; Sutriyanti, Ni Komang (Sphatika: Jurnal Teologi, 2023)
The Tri Kerangka Dasar Agama Hindu is the foundation of life for Hindus which is fundamental. As a reference for the implementation of religion, the Tri Kerangka Dasar Agama Hindu consists of three parts, namely tattva, susila, and ācāra. Morality is the basis of the behavior of a religious person whereas morality itself is the philosophical foundation regarding whether an action must be carried out or not following ethical behavior. The teaching of morality introduces Hindus to ethics, morals, and social ethics. Today there are cases of moral violations in the life of religious people. Indonesia with high heterogeneity visualizes how diverse the hustle and bustle of social society is. Hindus also experience problems within their bodies. Many devotees of various generations touch the Vedas very rarely. Even though reading the Veda is a form of religious literacy. Thus, this research aims to bring the Vedas closer to Hindus regarding their moral teachings in them. The research method in writing this article is the documentation method which explores reference sources from the sacred Vedic literature, both the Sruti Vedas and the Smrti Vedas. In this article one of the Vedic Sruti sections that is referred to is the Rigveda Samhita while in the Veda Smrti, this article refers to the holy book Bhagavad Gita. The result is that there is a crystallization of the two reference sources of Hindu literature, namely: the Value of Honesty, the Value of Unity, and the Value of Self-Control.